The assessment of the robustness of microRNAs from oral cytological scrapings. (25th August 2016) - Prasad, Gareema; Seers, Christine; Reynolds, Eric; McCullough, Michael J.
Abstract : Background: Sampling of suspect oral lesions in the general dental clinic may increase early carcinoma detection thus oral cancer survival rates. One means of lesion sampling that is an alternative to incisional biopsy is cytological scraping. MicroRNA alterations are also being explored as a means of diagnosing carcinoma as an alternative to histopathology. Methods: We obtained cytological scrapings using 10 strokes ('light') or 40 strokes ('heavy') from the buccal mucosa of one healthy subject using a dermatological curette. MicroRNA was isolated from oral cytological scrapings immediately, or the scrapings were stored in buffer or RNA later, at 4°C, room temperature or 36°C, from 1 to 7 days prior to RNA isolation. All scrape comparisons and test conditions were conducted in triplicate. MicroRNAs were measured using qRT–PCR. Results: MicroRNAs can be obtained from cytological scrapings independent of the number of strokes and can be measured using qRT–PCR after storage under all conditions tested. Conclusion: MicroRNAs are robust to a wide range of storage conditions that bodes well for use of cytological scrapings to be of use in a clinical setting as a chair side sampling method for suspect oral lesions.